Factors Associated with Completion of Pre–Kidney Transplant Evaluations - Siskind, Eric (Thieme Medical Publishers, 2014)
This study sought to examine various factors that may prevent transplant candidates from completing their transplant workup prior to listing. We reviewed the records of 170 subjects (cases = 100, controls 70) who were either on dialysis or had less than 20 mL/min creatinine clearance and were therefore candidates for preemptive transplantation. Approximately, 56% of preemptive patients completed their workup, while only 36% of patients on dialysis completed their workup. Our data revealed that factors contributing toward completion of workup included intrinsic motivation (four times more likely), lack of specific medical comorbidities (three times more likely), and preemptive status (two times more likely). Among patients on dialysis, intrinsic motivation (five times more likely) and absence of cardiovascular complications (four times more likely) were associated with completion. When comparing patients on dialysis to patients not on dialysis, there were significant differences between the two groups in distance from home to the transplant center, level of education, and presence of medical comorbidities. We believe that targeted interventions such as timely referral, providing appropriate educational resources, and development of adequate support systems, have the potential to improve workup compliance of patients with advanced chronic kidney disease, including those on dialysis.